The Political Slant of Web Portal News and the Implications Relating to the Fake News Phenomenon - Dongook Choi (Korea Development Institute (KDI), 2017)
The argument that the news selection of Korean web portals is politically biased lacks not only objective evidence but also discourse on what the causes are. If web portals provide a sufficient amount of variety in their news contents, it may be unnecessary to regulate the average bias. However, a cautious approach is needed when expanding algorithm-based news feed services as the selective consumption of personalized news will polarize public opinion, which in turn, will serve to further disseminate fake news. - Web portals have editing teams that select and assign news contents. - In the past, bias was commonly measured in a subjective or arbitrary manner. - The partisanship was measured strictly based on statistics and not the researcher's arbitrary judgement. - The political leanings of web portals measured on a specific time line is the result of public opinion of a certain event. - Web portals have an incentive to maximize their advertising profit by increasing the number of users' clicks. - Consumers tend to reduce additional news consumption in the news section when they agree less with the views of the posted article. - The political bias of portal news is related to the portal's profit structure. - Personalized news feed could take away the chance for consumers to experience the diversity of news contents. - The erosion of public trust in mainstream media and the increased use of SNS amplified the spread of fake news. - In Korea, web portal can serve as a checking mechanism that suppress the echo-chamber effect incurred by SNS. - Diversity indicators can be developed using the level of bias in portal news. - News with diverse perspectives should be made available via web portals.
Keywords: 330